Characterising Firewood and Charcoal Production and Marketing Systems in the Dryland Woodlands of Ethiopia - Gonche Girma; Abebaw Shimeles (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Rising woodfuel demand in Ethiopia — driven by population growth, urbanisation, poverty and unemployment — is depleting dryland woodlands, yet the people who produce and trade firewood and charcoal remain poorly characterised. Objective: To characterise woodfuel production and marketing across nine dryland sites in Ethiopia in order to inform sustainable demand- and supply-side management. Methods: A cross-sectional mixed-methods design combined a structured survey of 245 producers and traders with participatory rural appraisal, focus-group discussions and key-informant interviews, analysed within a Structure–Conduct–Performance framework using one-way ANOVA with η² and Tukey HSD, χ² with Cramér's V, multiple regression, principal component analysis and market-concentration indices (α = 0.05). Results: Charcoal producers (51.8%) and firewood collectors (29.0%) dominated a moderately concentrated sector (HHI = 3697; Shannon H′ = 1.18). Mean monthly charcoal income (12,492 ETB) significantly exceeded firewood income (8,656 ETB) (F = 137.1, p < 0.001, η² = 0.41). Production peaked in February (66.9%), January (63.8%) and August (51.0%); regression explained 41% of income variance (adjusted R² = 0.39, p < 0.001). Most firewood (77.9%) and charcoal (53.4%) sold in nearby towns; producers captured only 27.7% of the final charcoal price. Conclusion: Woodfuel is simultaneously a primary livelihood and an income-smoothing strategy; improved kilns, sustainable-harvesting licensing and better market access are needed to reconcile rural incomes with dryland-woodland conservation.